STUDENTS’ PERCEPTION ON THE USE OF VIDIO IN LEARNING ENGLISH AS A FOREGIN LANGUAGE DURING PANDEMIC - Muhammad Shabir; Chotrun Nada (ENGLISH, 2021)
The research is aimed at exploring the students’ perception on the use of video in learning English language during pandemic. It deploys a qualitative research framework with the instrument used for data collection include, diary and interviews. The participants were a group of English students at a Junior High School in Bogor. The findings show that the students perceived the use of video as an engaging, motivating, and interesting media for their language learning. Their positive perception on the use of video is based on some advantages offered by the video that covers motivation, engagement, flexibility, and operability. The result also affirms video can facilitate students’ language learning during the current Covid-19 pandemic. Therefore, it is suggested that using video is highly recommended in this situation where teaching and learning activities are required to be conducted online.